Pengawasan Pendistribusian Gas Lpg 3 Kg Oleh Dinas Perdagangan, Koperasi, Usaha Kecil dan Menengah Kota Padang Panjang - Melia Hendra; Mayarni Mayarni (Konstitusi : Jurnal Hukum, Administrasi Publik, dan Ilmu Komunikasi, 2024)
Lack of supervision carried out by the Padang Panjang City SME Cooperative Trade Service has resulted in several distribution problems such as the scarcity of 3 kg LPG gas, the selling price of 3 kg LPG gas exceeding the HET and the existence of bases that sell 3 kg LPG gas outside the Padang City area. Long. This research aims to find out what causes the scarcity of 3 kg LPG gas in Padang Panjang City, to analyze how supervision has been carried out by the SME Cooperative Trade Service and what are the inhibiting factors in the implementation of supervision using the supervision theory according to Maskan This research uses descriptive qualitative research with data collection methods used, namely interviews, observation and documentation. The results of this research indicate that the supervision of the distribution of 3 kg LPG gas carried out by the SME Cooperative Trade Service has not been carried out well and the factors causing the scarcity of 3 kg LPG gas in Padang Panjang City are the lack of 3 kg LPG gas quota, and the presence of unscrupulous bases who sell the gas out. Padang Panjang City area. The main inhibiting factor in this supervision is the lack of human resources in the Padang Panjang City SME Cooperative Service.